INDONESIA–AUSTRALIA MARITIME COOPERATION AND ITS IMPLICATION ON INDONESIA’S MARITIME SECURITY AND SOVEREIGNTY - Arcelinocent Emile Pangemanan; Anak Agung Banyu Perwita; Sudibyo Sudibyo (The Republic of Indonesia Defense University, 2022)
Global Maritime Fulcrum (GMF) has provided a roadmap for realizing Indonesia’s maritime security and sovereignty with an active contribution regionally and globally. The research method used in this research is content analysis, which is an approach in qualitative research that in research that refers to systematic data and text collections that can be managed to support the research itself. The rise of transnational maritime crime has a major impact on why Indonesia and Australia are keen on building trust through maritime cooperation, for it has the potential to disrupt and threaten national development, therefore this research aims to the mapped diplomatic mechanism through GMF, as a framework that hostess Indonesia–Australia Maritime Cooperation and its plan of actions in ensuring Indonesia’s maritime security and sovereignty. The maritime cooperation between Indonesia and Australia has improved the integrated defense and security capabilities of both countries through capacity building, although the plan of action will end in 2022, therefore harnessing the longevity of the maritime cooperation is considered crucial.